Pengaruh rasio likuiditas,struktur modal dan aktivitas terhadap pertumbuhan laba - Sirait, Hermin; Muttaqin, Pebriyanti Nur Azizah; Anggraeni, Devi; Christanti, Shenda Aprilia (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
This study was proposed to determine how much influence the liquidity ratio, capital structure and activity have on profit growth in food and beverage sub-sector companies. This study uses secondary data, the financial data of food and beverage sub-sector companies listed on the IDX for the period 2017 – 2021. The sample technique uses purposive sampling and the analytical tool technique uses simple linear and multiple linear regression. The results of this study indicate that liquidity ratio, capital structure rasio and activity ratio partially have no effect and are not significant on profit growth. The Liquidity ratio, capital structure rasio and activity ratio simultaneously also have no effect and are not significant on profit growth. The variables show no effect on profit growth, with an Adjusted R2 value of 0.029 (2.9%), which means that the variables, Current Ratio, Debt to Equity Ratio and Inventory Turnover, have no effect on profit growth of only 2.9 % while the remaining 97.1% is explained by other variables beyond this. Partially the quality of the liquidity ratio, capital structure and activities have no effect and are not significant on profit growth.